2020
DOI: 10.1590/0034-7167-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Low Chronic Self-Esteem and Low Situational Self-Esteem: a literature review

Abstract: Objective: to develop a literature review about low self-esteem and components of the nursing diagnoses Low Chronic Self-Esteem and Low Situational Self-Esteem in patients with depressed mood. Method: an integrative literature review carried out in the Pubmed portal and in the Scopus and Web of Science electronic bibliographic databases. Depression and self-esteem descriptors were used, resulting in 32 articles. Results: literature indicated 7 clinical indicators and 14 etiological factors for low self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…This low self-esteem is also highly correlated with depressive symptoms and suicidal ideation [37]. Depression and anxiety are frequently discussed together in research due to their high comorbidity rates [22,23,38].…”
Section: Discussionmentioning
confidence: 99%
“…This low self-esteem is also highly correlated with depressive symptoms and suicidal ideation [37]. Depression and anxiety are frequently discussed together in research due to their high comorbidity rates [22,23,38].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect to be considered is the lower incidence of diagnosis chronic confusion (0.62%), when compared to diagnosis acute confusion (2.09%), and it may be emphasized that CAPS is an important service for attending to crisis situations, and not only to persistent illnesses. Welcoming the mental health crisis in territorial services is an important indicator of quality of the care network (29) . In the model of psychosocial care to which CAPS is inserted, it is suggested that the approach to the crisis should take place with RAPS support, with an emphasis on community health services and in a perspective of transversal knowledge and power among team professionals multidisciplinary and users, for effective care to complex situations, such as moments of crisis in mental health (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that the self-declared brown elders have better self-esteem in our study may be associated with issues related to the "strength of racial identity", defined as the positive feeling of belonging and attachment to their identity (15) , which increases their self-esteem and acts to protect these people from the internalization of bad feelings resulting from discrimination (25) . Therefore, self-esteem is, in most cases, a psychological strategy for protection, adaptation, and coping with stressful events (26) .…”
Section: Discussionmentioning
confidence: 99%